Kurikulum Merdeka untuk Mewujudkan Generasi Z Berdaya Saing Society 5.0 - Mangesti, Widyo; Kismartini, Kismartini (Universitas Islam Kadiri, 2024)
Merdeka Belajar Kampus Merdeka Curriculum is the latest policy in Indonesia that prioritizes learning activities outside of campus/school life, with assessments predominantly focusing on the characteristics of Pancasila and diversity as the hallmarks of the Indonesian nation, and the alignment of graduate outputs with industry and entrepreneurship in accordance with global developments to prepare students for future careers. The gap between social life and current technological development makes curriculum innovation urgently necessary so that students can use technology wisely to solve social problems and play a role in community life. The concept of education towards outcome- based education in the era of society 5.0 has become an urgent need in the world of education. This literature review research found that the implementation of the Merdeka Curriculum faces more complex difficulties and challenges, considering that the application of this curriculum requires the active involvement of educational facilitators and students, which in practice has not been optimally achieved across all educational units. A capacity-building program for learning facilitators is needed, supported by educational units and relevant stakeholders, to improve time management skills, conduct clear and mutually agreed-upon learning orientations, create a culture of active involvement from all parties involved in the project, manage students' active participation in group work, collaborate with various parties including those outside the school, optimally utilize technology, and evaluate teacher and student projects using individual and group performance assessment methods, followed by preparation for the next project.